Perancangan Sistem Informasi untuk Estimasi Bobot Daging Sapi Berbasis Android (Yayasan Kawanad, 2022)
Calculation of the weight of an animal is very important because in the body of an animal there are many things that can be utilized, one of which is cattle. Therefore, beef cattle weigh the cattle in order to estimate the weight of the beef using a conventional method. However, this use is considered inefficient because the number of scales is very limited and it is not easy to carry around. Therefore, for the process of estimating the body weight of the cattle, it is very important for livestock owners to know the body weight of the cattle. Information System for Estimating Beef Weight Based on Android is designed on Android operating system with minimum API 22 (Lollipop) and target API 26 or 27 (Oreo). For testing the application will be carried out on Asus Zenfone 2 with the Marshmallow version of the Android operating system (API 23). In this case the method used is the Indonesian Winter Formula, namely by measuring the chest circumference and body length. Based on the test results on the design of information systems for estimating the weight of beef based on Android, it can be identified and can be concluded as follows; based on the results of testing and measurements on 5 (five) cows showing an accuracy value of up to 98.75%, and the results of measuring the body weight of the cow depend on the calculation of the length and chest circumference of the cow where the process will greatly affect the calculation results.